The interactive effects of control-value appraisals and academic emotions on achievement - Villavicencio, Felicidad T. (Animo Repository, 2010)
The study tested the assumptions of the control-value theory of achievement emotions (Pekrun, 2006). The interactive effects of control-value appraisals and academic emotions on achievement were examined in 1345 engineering students. The Academic Emotions Questionnaire-Math (Pekrun, Goetz, & Frenzel, 2005) was used to assess how positive (enjoyment and pride) and negative academic emotions (anger, anxiety, boredom, shame, and hopelessness) moderated the relationships between control-value appraisals and trigonometry achievement. The Control-Value Scales (Pintrich, Smith, Garcia, & McKeachie, 1991) was used to assess control appraisal (self-regulation, self-efficacy, and control beliefs) and value appraisal (task value, intrinsic goal, and extrinsic goal) in predicting achievement (final grade and test scores). Results showed that positive emotions and control-value appraisals positively predicted achievement, but negative emotions and extrinsic goal negatively predicted achievement. Positive emotions exerted enhancing moderated effects but negative emotions exerted buffering moderated effects. Results suggest that the relationship between control-value appraisal and achievement is strengthened for students with high levels of positive emotions as opposed to those with lower levels of positive emotions, but weakened for students with higher levels of negative emotions as compared to those with lower levels of negative emotions. Thus, the influence of control-value appraisals on achievement is facilitated or inhibited depending on the level of academic emotions.